Ericksonian hypnosis and hypnotherapy : a case study of two primary school children experiencing emotional difficulties - Daniels, Rene Alice (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MEdPsych (Educational Psychology))--University of Stellenbosch, 2005.